The genus Thaumatomyrmex Mayr 1887 in Mexico (Hymenoptera: Formicidae). - Rojas-Fernández, Patricia (Instituto de Ecología, A.C., 2009)
In this paper the distribution in Mexico of the ant genus Thaumatomyrmex is analyzed. The Los Tuxtlas region in the state of Veracruz represents the most northern locality for this rare Neotropical genus. Body measurements and photographs of the two specimens collected are provided; the status of the species remains unclear due to the lack of definition on the species diagnostic characters. Rarity of the genus in Mexico is discussed.